E-023 Patient access site preference in cerebral angiography. (23rd July 2017) - Snelling, B; Haniff, R; Caplan, J; Sur, S; Khandelwal, P; Yavagal, D; Starke, R; Peterson, E
Abstract : Introduction: Transradial access (TRA) is often the preferred approach for interventional cardiology procedures. Despite a preponderance of data demonstrating the improved safety of TRA over transfemoral access (TFA) in cardiology and large retrospective studies demonstrating the feasibility of TRA for cerebral angiography, the transradial approach has yet to gain large scale favor in neurointerventional procedures. Based on our positive initial institutional experience with TRA for mechanical thrombectomy in acute ischemic stroke intervention, we have adopted a "radial first" policy for cerebral angiography. In this study we evaluate patient preferences and experiences with TRA as compared to TFA. Methods: Telephone interviews were conducted with 58 consecutive patients following diagnostic cerebral angiography in which transradial access was used. Technical success was achieved in all cases and there were no major complications. Patients were assessed for wrist or arm and shoulder pain (ranked as none, mild, moderate, or severe). In addition, previous experience with transfemoral access (yes or no) and patient preference for a subsequent procedure (prefer radial, prefer femoral, or no preference) were assessed. Results81% of patients reported "None" or "Mild" wrist discomfort immediately following the procedure, while 97% of patients reported "None" or "Mild" arm and shoulder discomfort. 72% of patients (42/58) had undergone prior angiography with transfemoral access as well. In addition, 72% of all patients would prefer transradial access for their next procedure. Of patients who had experienced both transradial and transfemoral angiography previously, 78% (32/41) would prefer transradial access for their next procedure. Conclusion: Transradial access is preferred in a majority of patients, especially those who have undergone prior transfemoral angiography. Furthermore, a majority of patients experience little to no discomfort following transradial access for cerebral angiography. This data adds to a growing body of literature supporting a re-evaluation of the radial approach for neurointervention. Disclosures: B. Snelling: None. R. Haniff: None. J. Caplan: None. S. Sur: None. P. Khandelwal: None. D. Yavagal: None. R. Starke: None. E. Peterson: None.